ARCHITECTURE OF FARMERS' MARKETS IN UZBEKISTAN AND THEIR LOCATION IN THE URBAN STRUCTURE ON THE EXAMPLE OF ALOY MARKET - Juraeva Nilufar Khaydarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the historical role of the Aloy Bazaar in Tashkent, its current state, scientific and practical work on artistic and technical modernization, the current state of Western and Eastern architectural traditions, the place of the market in the urban structure.